2018
DOI: 10.1111/jac.12276
|View full text |Cite
|
Sign up to set email alerts
|

Assessing morphological characteristics of elite cotton lines from different breeding programmes for low temperature and drought tolerance

Abstract: Cotton breeders in the United States strive to develop region‐specific genotypes adapted to low temperatures and variable soil moistures during early‐season planting. Nine elite upland cotton germplasm (Gossypium hirsutum L.) lines, representing public breeding programmes from nine states across the cotton belt, were evaluated for cold and drought stresses during seed germination and seedling growth stages. Lines were subjected to three treatments, such as low temperature well‐watered (22/14°C, WW), optimal te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 36 publications
11
34
0
Order By: Relevance
“…These results for cultivar effects on seedling vigor are similar to the results from previous studies showing a positive relationship between seed mass, oil content, calorie content, and seedling vigor in cotton (Krieg & Bartee, 1975;Snider et al, 2014Snider et al, , 2016. A study was done by Singh et al (2018) on nine elite Upland cotton germplasm lines to determine the effect of low temperature conditions on seed germination and early seedling growth. The results from the study reported a negative effect of low temperature conditions on root and shoot growth in the early season growth stage.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These results for cultivar effects on seedling vigor are similar to the results from previous studies showing a positive relationship between seed mass, oil content, calorie content, and seedling vigor in cotton (Krieg & Bartee, 1975;Snider et al, 2014Snider et al, , 2016. A study was done by Singh et al (2018) on nine elite Upland cotton germplasm lines to determine the effect of low temperature conditions on seed germination and early seedling growth. The results from the study reported a negative effect of low temperature conditions on root and shoot growth in the early season growth stage.…”
Section: Discussionsupporting
confidence: 87%
“…A study was done by Singh et al. () on nine elite Upland cotton germplasm lines to determine the effect of low temperature conditions on seed germination and early seedling growth. The results from the study reported a negative effect of low temperature conditions on root and shoot growth in the early season growth stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being immobile, they are capable of developing certain mechanisms to detect environmental changes and respond to environmental conditions. Plants show morphological and physiological adaptations in response to environmental conditions [4,14,31,32]. For instance, the reproductive development of many crop species is damaged by heat in a way that they produce no viable pollen or no flowers [33][34][35], or if they produce flowers, they may set no fruit or seed [3,4,6,11].…”
Section: Discussionmentioning
confidence: 99%
“…After separating the stem from the root system of each plant, roots were washed with water on a sieve [37,38,39]. Washed roots were scanned with a WinRhizo Pro optical scanner (Regent Instruments, Inc., QC, Canada) by floating the individual root system in 5 mm of water in a Plexiglas tray [39,40]. Gray-scale root images were acquired by setting the parameters to high accuracy (resolution 800 × 800 dpi), and the images were analyzed using WinRhizo Pro software.…”
Section: Methodsmentioning
confidence: 99%